Model Pengembangan Pembelajaran PJBL Berbasis Proyek untuk Meningkatkan Kreatifitas Siswa - Nana Misrochah (ILIN Institute Makassar, 2021)
Through this research, it is hoped that acid-base titration learning will be more meaningful and can contribute to student creativity. PjBL model is an integrated learning that is carried out cooperatively through projects that develop student skills, so that student creativity will increase. The project given in this research is making of soap from the wrinkled oil. In the process can be attributed to the application of acid-base titration material by calculation of acid numbers and saponification numbers on the cooking oil before being processed into soap. The results of data analysis shows data significance> 0.05 which means that the data is normally distributed for pretest and posttest. The data of paired sample t-test shows that the significance obtained is 0,000 <0.05 which means that there is a significant difference between the mean value of the integrated creativity test with the acid-base titration concept before treatment is given after treatment is given. Creativity improvement were calculated using the N-Gain value resulting in an average achievement rate of 0.50 and belonging to the moderate category. Posttest results indicate that the implementation of project-based LKP is effective in improving student creativity with classically average is 81.5%.